The Effect of Soaking Layer Eggs into Boiled Water of Melinjo (Ggnetum gnemon l.) Leaves against Oxidation, Foaming, and Internal Quality of Eggs - Diky Kurniawan; Edi Soetrisno; Suharyanto Suharyanto (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2021)
This study aimed to evaluate the effect of soaking layer eggs into boiled water of melinjo leaves on oxidation, foaming, and internal quality of eggs. The experimental design was a Completely Randomized Design with 4 treatments namely without any soaked (P0), soaked for 24 h into boiled water of melinjo leaves 15% (P1), 30% (P2), and 45% (P4) with 4 replications. The measurements were on the 14th and 21st days. The data were analyzed using ANOVA and DMRT multiple comparisons by significance of 0.05. The observed variables included peroxide value, moisture content, foam, albumen and yolk (weight, volume, and index), air sac, and haugh unit. The results showed that the immersion into the boiled water of melinjo leaves had an effect on water content, oxidation rate, foam stability and internal quality of eggs with the best concentration was 30% (P2) and 45% (P3), but had no effect on foam formation. It was concluded that the immersion of chicken eggs at concentrations of 30% (P2) and 45% (P3) was able to prevent the acceleration of the changes in moisture content, suppress oxidation, improve the foam stability, and maintain the internal quality of eggs until the 21st day.